2013
DOI: 10.1175/jtech-d-13-00071.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Intercomparison between Suomi-NPP VIIRS and Aqua MODIS Reflective Solar Bands Using Simultaneous Nadir Overpass in the Low Latitudes

Abstract: On-orbit radiometric performance of the Suomi National Polar-Orbiting Partnership (Suomi-NPP) Visible Infrared Imaging Radiometer Suite (VIIRS) is studied using the extended simultaneous nadir overpass (SNO-x) approach. Unlike the traditional SNO analysis of data in the high latitudes, this study extends the analysis to the low latitudes-in particular, over desert and ocean sites with relatively stable and homogeneous radiometric properties-for intersatellite comparisons. This approach utilizes a pixel-by-pixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…Likewise, the remaining bias between R 2.1,aA and R 2.1,M is about 0.3 %. These values are in the range of the intercomparison results by Uprety et al (2013), who reported radiometric bias uncertainties between the Suomi National Polar-Orbiting Partnership (Suomi NPP) VIIRS and MODIS in the range of 2-3 % for the VNIR and SWIR bands. It is important to note that small differences in cloud top reflectances could result in possibly large differences in retrieved cloud properties.…”
Section: Reflectance Comparison For C14 and C19supporting
confidence: 54%
“…Likewise, the remaining bias between R 2.1,aA and R 2.1,M is about 0.3 %. These values are in the range of the intercomparison results by Uprety et al (2013), who reported radiometric bias uncertainties between the Suomi National Polar-Orbiting Partnership (Suomi NPP) VIIRS and MODIS in the range of 2-3 % for the VNIR and SWIR bands. It is important to note that small differences in cloud top reflectances could result in possibly large differences in retrieved cloud properties.…”
Section: Reflectance Comparison For C14 and C19supporting
confidence: 54%
“…Although not all DT bands have been compared consistently, the general conclusion was that at least some of the VIIRS bands appear to be biased high as compared to MODIS. The Uprety et al (2013) study indicated that the VIIRS M4 (0.55 µm), M5 (0.67 µm), M7 (0.86 µm) and M8 (1.24 µm) bands had residual high biases of 1.6, 1.3, 2.2 and 3.5 %, respectively, (with error bars of 1-2 %). Based on personal communication, S. Uprety (2014) suggested that the M11 band (2.26 µm) also appears to have a high bias, but more study was required.…”
Section: Calibrationmentioning
confidence: 96%
“…For example, aerosols have decreased dramatically over eastern Europe and increased over India and China (Chin et al, 2013). Regional aerosol changes (Zhang and Reid, 2010) affect regional weather and local air quality, with regional effects having global consequences, including health (e.g., van Donkelaar et al, 2010) and economic consequences (Lin et al, 2014). Therefore, it is imperative that the community has a consistent, long-term aerosol data set, which is global in construct, but with resolution and accuracy sufficient to resolving regional trends.…”
Section: R C Levy Et Al: Long-term Global Aerosol Optical Depth Rementioning
confidence: 99%
See 2 more Smart Citations